The Black Legend : George Bascom, Cochise, and the start of the Apache Wars - Hocking, Doug (TwoDot, 2019)
In 1861, war between the United States and the hostile Chiricahua Apaches seemed inevitable. When a young boy was kidnapped from his stepfather's ranch, Lieutenant George Bascom confronted Apache leader Cochise, setting the smoldering conflict ablaze. This book examines the legend and provides a new analysis of Bascom and Cochise's behavior within the historical context of the Indian Wars.